Incidencia de un recurso educativo abierto en el aprendizaje de estudiantes del Colegio de Bachillerato Pasaje - Reyes Estrada, Cleider Vicente (Machala, Universidad Técnica de Machala, 2022)
This research collects a synthesis of the deep and intense debate that takes place around the training process at the level of secondary education, with particular emphasis on the teacher and students of the Baccalaureate, where not only must they have conventional or traditional pedagogical and didactic resources, if not also pedagogical and technological didactic resources. The research is structured in chapters, where the approaches, reviews and analysis of recent and contemporary research on Open Educational Resources and their impact on teacher teaching and student learning in the subject of Biology of the first year of parallel Baccalaureate are collected. A' of the Colegio Pasaje in the Informatics Professional Figure. Pedagogical and didactic methodological strategies were used with the help of technological and digital tools, for its application Design-Based research was used, the same one that is directed at the innovation of the teaching-learning processes of the educational promoters and change stereotypes to Through technological Open Educational Resources, achieving pedagogical incidence and encouraging active participation in students inside and outside their classroom. For a better understanding of the readers, the research document has been designed with a structure of three chapters. Chapter I, we can find the diagnosis of needs and requirements, description of the context, facts of interest as well as the approach to the research problem, research objectives, place of performance, population and sample, research approach, method of research, description of the requirements/needs that the prototype must solve, referential framework and state of the art. Chapter II, we locate the prototype and its definition, objective of the prototype, theoretical foundation of the prototype, analysis, design, development, implementation, evaluation and characteristics of the prototype. Chapter III, we can find the results of the evaluation of the research through experience I and experience II, the same ones that were planned and evaluated with the data collection instruments such as the interview guide, observation note and the same surveys. that were elaborated based on the independent and dependent variable and its dimensions and indicators. V For the design of the Open Educational Resource, the Analysis, Design, Development, Implementation and Evaluation (ADDIE) methodology was used, which allowed a detailed analysis of the basic requirements of technology in education based on the objectives of the research. The present investigation is constituted by a sample of 28 students of the First Parallel Baccalaureate "A" of the Computer Professional Figure of the Baccalaureate College "Pasaje" with an average age of 15 years and a teacher of the subject of Biology, to determine the level of pedagogical incidence of the Open Educational Resource, evaluation instruments were applied such as the interview guide, field note and survey. In conclusion, the use of Open Educational Resources in the teacher's teaching processes and student learning brings benefits such as pedagogical incidence, active motivation, autonomous work and changes in learning environments.
Está investigación recoge una síntesis del profundo e intenso debate que transcurre al rededor del proceso formativo a nivel de la educación media, con partícula énfasis en el docente y estudiantes del Bachillerato, donde no solo ha de poseer recursos pedagógicos y didácticos convencionales o tradicionales, si no también recursos pedagógicos y didácticos tecnológicos. La investigación está estructurada en capítulos, donde se recoge los planteamientos, revisiones y análisis de investigaciones resientes y contemporáneas sobre Recursos Educativos Abiertos y su incidencia en la enseñanza del docente y el aprendizaje del estudiante en la asignatura de Biologías del primer año de Bachillerato paralelo “A’ del Colegio Pasaje en la Figura Profesional Informática. Se utilizó estrategias pedagógicas y metodológicas didácticas con la ayuda de herramientas tecnológicas y digitales, para su aplicación se utilizó la investigación Basada en Diseño, la misma que esta direccionada en la innovación de los procesos de enseñanza-aprendizajes de los promotores educativos y cambiar estereotipos a través de los Recursos Educativos Abiertos tecnológicos logrando la incidencia pedagógica e incentivado la participación activa en los estudiantes dentro y fuera de su aula de clase. Para una mejor comprensión de los lectores el documento de investigación se ha diseñado una estructura de tres capítulos Capítulo I, podemos encontrar el diagnóstico de necesidades y requerimientos, descripción del contexto, hechos de interés como también el planteamiento del problema de la investigación, Objetivos de la investigación, lugar de realización, la población y muestra, enfoque de la investigación, método de investigación, descripción de los requerimientos/necesidades que el prototipo debe de resolver, Marco referencial y Estado de Arte. Capítulo II, localizamos el prototipo y su definición, objetivo del prototipo, Fundamentación teórica del prototipo, análisis, diseño, desarrollo, implementación, evaluación y características del prototipo. Capítulo III, podemos hallar los resultados de la evaluación de la investigación a través a la experiencia I y experiencia II las misma que fueron planificadas y evaluadas con los instrumentos de recolección de datos como la guía de entrevista, nota de observación y la encuestas los mismos que fueron elaborados en base a la variable independiente y dependiente y sus dimensiones e indicadores. III Para el diseño del Recurso Educativo Abierto se utilizó la metodología de Análisis, Diseño, Desarrollo, Implementación y Evaluación (ADDIE) lo que permitió hacer un análisis minucioso de requerimientos básicos de la tecnología en la educación en base a los objetivos de la investigación. La presente Investigación está constituida por una muestra de 28 estudiantes del Primero de Bachillerato Paralelo “A” de la Figura Profesional Informática del Colegio de Bachillerato “Pasaje” con edad promedia de 15 años y una docente de la asignatura de Biología, para determinar el nivel de incidencia pedagógica del Recurso Educativo Abierto se aplicó instrumentos de evaluación como la guía de entrevista, nota de campo y encuesta. A manera de conclusión, el uso del Recursos Educativo Abierto en los procesos de enseñanza del docente y el aprendizaje del estudiante trae beneficios como incidencia pedagógica, motivación activa, trabajo autónomos y cambios de ambientes de aprendizajes.
Keywords: RECURSO EDUCATIVO ABIERTO; INCIDENCIA PEDAGOGICA; METODOLOGIA DE ENSEÑANZA; MOTIVACION ACTIVA